Experience XSI 4 the official Softimage XSI 4 guide to character creation - Sims, Aaron (Gale virtual reference library, 2004)
This book will help you understand and work with XSI 4 to create a highly detailed character in a production environment. The approach in this book is unique because it is the result of a collaboration between art and technology.